The effects of pre-drying treatments and different drying methods on nutritional and sensory quality and drying characteristics of moringa leaves (Moringa oleifera lam.) - Koo, M.W. (2016)
The combination of pre-treatment and different drying methods can affect the quality of M. oleifera leaves. The aim of this research was to determine the effect of the blanching pre-treatment prior to the drying methods of oven and solar drying on the nutritional and sensory quality, and drying characteristics of M. oleifera leaves. The results showed that blanching allowed better retention of colour and chlorophyll but not ascorbic acid. However, drying at a low temperature of 35 °C allowed a significantly (p < 0.05) higher amount of ascorbic acid to be retained after blanching. Based on the accelerated storage studies of 15 days, the amount of ascorbic acid significantly (p < 0.05) reduced by more than 50%, regardless of whether the dried M. oleifera leaf powder were placed in PP or PET packaging, under the sun or in the shade . Due to the sensitive nature of ascorbic acid, the blanching process does not contribute much to ascorbic acid retention during storage. The chlorophyll pigments however, were successfully retained after the blanching and drying process. The total chlorophyll content was maintained after 15 days of storage and no significant (p > 0.05) difference was noted. Colour is correlated to chlorophyll, therefore, when chlorophyll pigments are retained, so is the green visual of the M. oleifera leaves. Due to the time constraint, the sensory quality was only achieved for unblanched versus blanched M. oleifera leaf powder. Participants noted a stonger and more pungent lingering taste and after taste for the unblanched M. oleifera leaf powder. Most participants preferred the milder taste of the blanched M. oleifera leaf powder. Overall, the results suggest that the blanching treatment and a drying process using a low temperature is best suited for nutrient retention and overall acceptability for consumption. Therefore, this processing method may be utilised on the large scale for producing nutritious M. oleifera leaf products.